Morphology, structure, and electrochemical properties of the MnOx@CNTs composite: a study of SEM, EDX, XPS, and CVA methods - P. M. Korusenko; S. N. Nesov; K. E. Ivlev (Омский научный вестник)
In this work, we carried out a comprehensive study of the morphology, chemical composition, electronic structure, and electrochemical characteristics of a nanocomposite based on carbon nanotubes (CNTs) and manganese oxide particles. The study of the electronic structure of the nanocomposite, performed by X-ray photoelectron spectroscopy (XPS), showed that manganese is in two chemically nonequivalent states in MnO2-x and in KMnO4 . It has been established that manganese oxide is deficient in oxygen. In the course of electrochemical tests performed by the method of cyclic voltammetry (CVA), it is shown that the electrode based on the nanocomposite showed high arial capacitance values of 320 mF∙cm–2 at a potential scan rate of 5 mV∙s–1 and a low gravimetric capacitance of 14 F∙g–1. With an increase in the potential scan rate, the specific capacitance of the nanocomposite significantly decreased relative to CNTs, which is due to a number of reasons: (i) insufficient porosity of the electrode surface; (ii) a decrease in the amount of MnOx nanoparticles in the electrode and their dissolution in the electrolyte during charge-discharge processes.